2020
DOI: 10.1002/jcu.22915
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of dobutamine stress echocardiography in symptomatic high gradient aortic stenosis patients scheduled for transcatheter aortic valve implantation

Abstract: Purpose We aimed to study the safety and feasibility of low‐dose dobutamine stress echocardiography in a symptomatic high gradient aortic stenosis population scheduled for transfemoral transcatheter aortic valve implantation (TAVI) and to quantify left ventricular (LV) flow reserve. Methods Fifty patients underwent dobutamine stress echocardiography with 5 minutes increments of 5 μg/kg/min up to 20 μg/kg/min until the heart rate increased ≥20 beats/min from baseline or exceeded 100 beats/min. Other criteria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Barbash et al ( 21 ) in 61 patients with LFLG AS undergoing TAVI showed that CR assessed with dobutamine SE did not predict LVEF recovery but did predict lower mortality ( 21 ). Saevik et al ( 22 ) demonstrated safety and feasibility of low-dose dobutamine SE in 50 patients with high gradient AS, showing reduced CR in 40% of them ( 22 ). Finally D’Andrea et al ( 23 ) showed that a cutoff value for left ventricle global longitudinal strain (LV GLS) of >−12% well distinguished patients without significant CR and with lack of positive remodeling after TAVI at follow-up ( 23 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Barbash et al ( 21 ) in 61 patients with LFLG AS undergoing TAVI showed that CR assessed with dobutamine SE did not predict LVEF recovery but did predict lower mortality ( 21 ). Saevik et al ( 22 ) demonstrated safety and feasibility of low-dose dobutamine SE in 50 patients with high gradient AS, showing reduced CR in 40% of them ( 22 ). Finally D’Andrea et al ( 23 ) showed that a cutoff value for left ventricle global longitudinal strain (LV GLS) of >−12% well distinguished patients without significant CR and with lack of positive remodeling after TAVI at follow-up ( 23 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In classic high-gradient AS, SE is not usually performed and there is little data about it. Saevik et al ( 22 ) published an initial analysis of a cohort of patients with symptomatic high-gradient AS and LVEF > 40% in which pre-procedural CR was evaluated with a low-dose DSE pre-TAVI. The aim was to evaluate the safety and feasibility of the DSE in this subset of patients and look for the presence of CR ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations